Ritual Alo pada Masyarakat Cia-Cia Burangasi Kabupaten Buton - Janu, La (UIN Maulana Malik Ibrahim Malang, 2012)
This research examined alo ritual in Cia-Cia community Burangasi Buton, South East Celebes Province. This research is conducted to identify answers for the concerning problems described of its present the importance of alo ritual in even the whole community. This study used a qualitative research method with participal observation and in depth interview as data collecting method. While data analysis, was done through ethnographic analysis technique. Alo ritual was carried out by reason of mental pressure or mental crisis caused by the death in family member. They concern about safety of spirit of the death given that the spirit has to experience a long and dangerous passage. They believe that this spiritually dangerous crisis time is not about the death only but covering up the whole family and even the whole community. In general, alo ritual had a purpose to normalize the unstable life condition of the family because of a death through deconstructing the existing life condition and reconstructing it into the brand new one at the same time. In such condition of brand new life, daily activities seem harmonious and normal without any fears, distress, depressed and so on. Penelitian ini fokus pada upacara alo yang terjadi di masyarakat Cia-Cia Burangasi Buton, Propinsi Celebes Tenggara. Penelitian ini dilakukan untuk mengidentifikasi jawaban-jawaban atas problematika penting terkait upacara alo dalam sebuah komunitas. Kajian ini menggunakan metode kualitatif dengan observasi partisipatoris dan wawancara mendalam sebagai teknik pengumpulan data. Data yang telah terkumpul kemudian dianalisa dengan teknik analisis etnografi. Upacara alo dilakukan dengan alasan ketertekanan jiwa dan krisis mental yang disebabkan karena kematian salah satu anggota keluarganya. Mereka berkonsentrasi terhadap keselamatan arwah dari sang mayat yang akan melalui lintasan panjang berbahaya. Mereka berkeyakinan bahwa saat yang membahayakan bagi arwah ini tidak hanya menimpa si mayat saja, melainkan juga seluruh anggota keluarga bahkan seluruh masyarakat. Secara umum, upacara alo bertujuan untuk menormalkan keadaan hidup yang tidak stabil akibat kematian si mayat. Dalam keadaan hidup yang baru ini, kegiatan sehari-hari nampak harmoni dan stabil tanpa ketakutan, penderitaan, tekanan, dan seterusnya.